Effectiveness of extracorporeal shock wave lithotripsy on intrahepatic biliary calculi developing after choledochal cyst surgery: A case report - Şenyüz, Osman Faruk; Gülşen, Fatih; Gökhan, Okan; Emre, Şenol; Eroğlu, Egemen (Turkish Journal of Gastroenterology, 2015)
Abstract The development of intra- and extrahepatic bile duct stones has been reported as one of the most serious complications after choledochal cyst excision with biliary-enteric reconstruction through Roux-en-Y hepaticojejunostomy (HJ). Here, we report our experience with extracorporeal shock wave lithotripsy (ESWL) in a case of giant intrahepatic stones developing after choledochal cyst surgery. ESWL is an excellent therapeutic modality for large intrahepatic biliary calculi, and after dilating the HJ anastomosis percutaneously, it can be offered as first-line therapy to these patients.